Irisin Mitigates Oxidative Stress, Chondrocyte Dysfunction and Osteoarthritis Development through Regulating Mitochondrial Integrity and Autophagy - Feng-Sheng Wang; Chung-Wen Kuo; Jih-Yang Ko; Yu-Shan Chen; Shao-Yu Wang; Huei-Jing Ke; Pei-Chen Kuo; Chin-Huei Lee; Jian-Ching Wu; Wen-Bin Lu; Ming-Hong Tai; Holger Jahr; et al. (Antioxidants, 2020)
Compromised autophagy and mitochondrial dysfunction downregulate chondrocytic activity, accelerating the development of osteoarthritis (OA). Irisin, a cleaved form of fibronectin type III domain containing 5 (FNDC5), regulates bone turnover and muscle homeostasis. Little is known about the effect of Irisin on chondrocytes and the development of osteoarthritis. This study revealed that human osteoarthritic articular chondrocytes express decreased level of FNDC5 and autophagosome marker LC3-II but upregulated levels of oxidative DNA damage marker 8-hydroxydeoxyguanosine (8-OHdG) and apoptosis. Intra-articular administration of Irisin further alleviated symptoms of medial meniscus destabilization, like cartilage erosion and synovitis, while improved the gait profiles of the injured legs. Irisin treatment upregulated autophagy, 8-OHdG and apoptosis in chondrocytes of the injured cartilage. In vitro, Irisin improved IL-1β-mediated growth inhibition, loss of specific cartilage markers and glycosaminoglycan production by chondrocytes. Irisin also reversed Sirt3 and UCP-1 pathways, thereby improving mitochondrial membrane potential, ATP production, and catalase to attenuated IL-1β-mediated reactive oxygen radical production, mitochondrial fusion, mitophagy, and autophagosome formation. Taken together, FNDC5 loss in chondrocytes is correlated with human knee OA. Irisin repressed inflammation-mediated oxidative stress and extracellular matrix underproduction through retaining mitochondrial biogenesis, dynamics and autophagic program. Our analyses shed new light on the chondroprotective actions of this myokine, and highlight the remedial effects of Irisin on OA development.